Perception of Intellectual Stimulation, Reliability and Proactiveness among Health Managers Working In Tertiary Level Hospitals (Journal of Fatima Jinnah Medical University, 2018)
Background: Needs and priorities in public health require leaders who are able to engage in systems thinking, including analytical and critical thinking processes, visioning of potential futures, strategic and tactical assessment, and communication and change dynamics. New public health, in the back drops of globalization, financial strain, shifting power basis and serious demands on an already stressed system; needs visionary leadership.Objective: To assess perception of health managers regarding Intellectual stimulation and its variables.Methods: A Qualitative study was conducted in two public sector tertiary level hospitals in Lahore. Data collection was done by means of observation and in- depth interviews. Multifactor Leadership Questionnaire (MLQ) was taken as benchmark and an open ended questionnaire was developed on its lines. One main domain of Intellectual stimulation along with its two variables was developed and emergence of different themes and categories was noted.Results: In the domain of Intellectual stimulation all 17 participants of the study showed positive themes regarding reliability which was supported by their work life examples. On the other hand out of the total, six health managers did not have any idea about proactiveness. Female health managers were more inclined towards transformational leadership behavior.Conclusion: Health managers with Administration/ Management degree had a clear and better concept of Intellectual stimulation as a pillar of transformational leadership and had clear perception regarding the variables of reliability. In contrast few had a clear idea about the variable of proactiveness. Female health managers were found to have greater perception and application of transformational leadership behavior; thus taking enhanced output as a team leader.
Keywords: Intellectual stimulation, reliability, proactiveness health managers.